Scalable Simulation of 3D Wave Propagation in Semi-Infinite Domains Using the Finite Difference Method on a GPU Based Cluster - Sabino, Thales Luis Rodrigues; Zamith, Marcelo; Brandão, Diego; Montenegro, Anselmo; Clua, Esteban; Kischinhevksy, Maurício; Leal-Toledo, Regina C. P.; Silveira Filho, Otton T.; Bulcão, André (Anais do Brazilian e-Science Workshop (BreSci), 2011)
The scattering of acoustic waves has been of practical interest for the petroleum industry, mainly in the determination of new oil deposits. A family of computational models that represent this phenomenon is based on finite difference methods. The simulation of these phenomena demands a high computational cost and large amounts of available memory. In this work we employ GPU based cluster environment for the development of scalable solvers for a 3D wave propagation problem with finite difference methods.